2002
DOI: 10.1007/s00466-002-0306-2
|View full text |Cite
|
Sign up to set email alerts
|

Weight and crash optimization of foam-filled three-dimensional ?S? frame

Abstract: The optimization process with the target of minimum weight design of a foam-filled three-dimensional thin-walled S frame under the prescribed values of stiffness and energy absorption was formulated and solved. A distinctive feature of the present approach is that the response function is given as an analytical expression. Three design parameters were introduced in this study, which are the width of the column wall, gauge thickness, and the relative foam density. The sequential quadratic programming (SQP) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…The results reveal that, the optimum values have been taken place at the upper or lower bounds. These values are indeed the usual values taken in the literatura (khalkhali, 2015;Elmarakbi et al, 2013;Han and Yamazaki, 2001;Kim et al, 2002). It is evident that changing the lower and upper bounds would probabaly give different results.…”
Section: Parametric Studysupporting
confidence: 63%
“…The results reveal that, the optimum values have been taken place at the upper or lower bounds. These values are indeed the usual values taken in the literatura (khalkhali, 2015;Elmarakbi et al, 2013;Han and Yamazaki, 2001;Kim et al, 2002). It is evident that changing the lower and upper bounds would probabaly give different results.…”
Section: Parametric Studysupporting
confidence: 63%
“…Recently, much attention is given to the cellular material filled thin-walled structures (Chen, 2001;Hanssen et al, 2002;Kim et al, 2002;Santosa and Wierzbicki, 1999;Seitzberger et al, 2000). The studies showed that the interaction between metal or polymeric cellular material fillers and the supporting structures produces some desirable crushing behaviors and energy absorption properties.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectional dimensions and material properties are the main considerations used to determine the stiffness, strength and energy absorption of box-type structures. Kim et al [9] applied loads to hydro-aluminum foam-filled S-shaped tubes. From the deformation pattern of the S-shaped tube, they concluded that ultra-light metallic foam-filling is a good way to strengthen S-frame members.…”
Section: Introductionmentioning
confidence: 99%